2010
DOI: 10.1088/0957-4484/21/38/385201
|View full text |Cite
|
Sign up to set email alerts
|

Magnetism and perfect spin filtering effect in graphene nanoflakes

Abstract: Magnetic and spin-polarized transport properties in zigzag-edged graphene nanoflakes were investigated from first-principles calculations. Ferrimagnetic structure was found to be the ground state for triangular shaped graphene flakes. Magnetism is weakened by doping B or N atoms into the flakes, and it is enhanced if F atoms are doped in certain sublattices of the flakes. The magnetic properties can be rationalized by the behaviors of dopants as well as interactions between dopants and the host atoms. A perfec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
42
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 36 publications
1
42
0
Order By: Relevance
“…15,16 In particular, it has been proposed that the magnetic states of graphene nanostructures can be exploited for the realization of spintronic devices, e.g., spin filters 12,13,17,18 and logic gates 16,19 with graphene functional blocks. Recent investigation 14,20 suggested that the magnetic ordering of the ZZ edges in GNF can be tuned by carrier doping.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 In particular, it has been proposed that the magnetic states of graphene nanostructures can be exploited for the realization of spintronic devices, e.g., spin filters 12,13,17,18 and logic gates 16,19 with graphene functional blocks. Recent investigation 14,20 suggested that the magnetic ordering of the ZZ edges in GNF can be tuned by carrier doping.…”
Section: Introductionmentioning
confidence: 99%
“…Recently [4][5][6][7][8], it has been shown that such edge-spin polarization can be engineered by functionalization with transition metals [4], biasing the ribbons [5,6], and by doping [7] to induce a half-metallic [9][10][11][12] band structure. For example, in a pioneering experimental study [10], the half-metallicity has been achieved by applying in-plane homogeneous electric fields across the zigzag-shaped edges of the GNRs.…”
mentioning
confidence: 99%
“…The weak intrinsic spin-orbit coupling and long spin diffusion lengths suggest graphene as an ideal spintronic material [1][2][3][4][5][6][7][8][9][10]. Spin splitting or filtering in graphene is predicted for half-metallic nanoribbons [2,[11][12][13] [24][25][26], and, in particular, nanostructured zigzag (zz)-edged devices [11][12][13]15,16,[27][28][29][30][31][32][33] are among the proposed graphene-based half metals. Spin filters have been proposed using triangular dots [15,31] or perforations [29] with many similarities, e.g., low-energy localized magnetic states and a net sublattice imbalance.…”
mentioning
confidence: 99%
“…The zz-edged structures support local ferromagnetic moments [3], however, global ferromagnetism is induced when the overall sublattice symmetry of the edges is broken [11][12][13]16,27,28,45]. This occurs for zzedged triangles [15,[29][30][31][32][33]. We have recently discussed the electronic structure of triangular graphene antidot lattices (GALs) [33]-here, we focus on transport through devices…”
mentioning
confidence: 99%
See 1 more Smart Citation